Preparation of a Molecularly Imprinted Polymer on Polyethylene Terephthalate Platform Using Reversible Addition-Fragmentation Chain Transfer Polymerization for Tartrazine Analysis via Smartphone - Hernández, Christian Jacinto; Medina, Raúl; Maza Mejía, Ily; Hurtado, Mario; Khan, Sabir; Picasso, Gino; López, Rosario; Sotomayor, María D. P. T. [UNESP] (MDPI, 2024)
This work describes the preparation of a molecularly imprinted polymer (MIP) platform on polyethylene terephthalate (MIP-PET) via RAFT polymerization for analyzing tartrazine using a smartphone. The MIP-PET platform was characterized using Fourier transform infrared (FTIR) techniques, Raman Spectroscopy, X-ray photoelectron spectroscopy (XPS), and confocal microscopy. The optimal pH and adsorption time conditions were determined. The adsorption capacity of the MIP-PET plates with RAFT treatment (0.057 mg cm−2) was higher than that of the untreated plates (0.028 mg cm−2). The kinetic study revealed a pseudo-first-order model with intraparticle diffusion, while the isotherm study indicated a fit for the Freundlich model. Additionally, the MIP-PET demonstrated durability by maintaining its adsorption capacity over five cycles of reuse without significant loss. To quantify tartrazine, images were captured using a smartphone, and the RGB values were obtained using the ImageJ® free program. A partial least squares regression (PLS) was performed, obtaining a linear range of 0 to 7 mg L−1 of tartrazine. The accuracy of the method was 99.4% (4.97 ± 0.74 mg L−1) for 10 samples of 5 mg L−1. The concentration of tartrazine was determined in two local soft drinks (14.1 mg L−1 and 16.5 mg L−1), with results comparable to the UV–visible spectrophotometric method.
Keywords: digital image colorimetry (DIC); PET; RAFT polymerization; smartphone; tartrazine